Training effects of Interactive Metronome® on golf performance and brain activity in professional woman golf players - Kim, J. H.; Han, J. K.; Han, D. H. (Human Movement Science, 2018)
During putting in golf, the direction and velocity of the club head should be consistent across swings. In order to maintain consistency in swing timing, the cerebellum provides temporal information, motor timing, control of rhythm, and timing of movements. We utilized Interactive Metronome (IM), a brain training software program that combines the concepts of neurotechnology with the abilities of a computer, to improve an individual`s rhythm and timing. We propose that IM would activate neural networks involved in decreasing variation in putt swing. Twenty professional female golfers (KLPGA) were randomly assigned to either an IM training group (n=10, 35-40min per session, twice a week for 6weeks) or a control group (n=10). The golf putting movements and brain activity were analyzed using Kinovea Software and resting state functional MRI, respectively. Consistency was measured as the standard deviation of mean swing speed (SSD) during three sections of the swing: backswing (AD-BS), backswing-impact (BS-IMP), and impact-finish (IMP-FIS). Our results show that the consistency of the IM group improved in the time between the back swing and impact in the 2m putt and 5m putt compared to the control group. Using functional MRI, after the training period, the IM group showed increased functional connectivity from the superior cerebellar vermis to the right medial frontal gyrus, left superior temporal gyrus, right middle occipital gyrus, right middle temporal gyrus, right cingulate gyrus, and right supramarginal gyrus (uncorrected p<0.001, voxels>40). These findings suggest that IM training in professional female golf players may improve consistency in putt timing. In addition, IM training may increase brain connectivity from the cerebellum to the frontal cortex, which plays an important role in motor control and timing. AUTORREFERAT